Corruption and Foreign Direct Investment. Evidence from Central and Eastern European States - Cristina Mihaela Amarandei (CES Working Papers, 2013)
This paper examines the impact of corruption on foreign direct investment inflows for ten Central and Eastern European states. The paper attempts to answer the question: what is the role of corruption in attracting foreign direct investments? Using the data from UNCTAD for foreign direct investment and Corruption Perception Index from Transparency International, for a period of 12 years, 2000-2012, we evaluate the specific impact of corruptions on FDI using GDP as control variable. Our results confirm the majority of literature and show a negative significant relation between the variables analyzed, but at a lower intensity than expected.
Keywords: D73; E02; F21; 330; foreign direct investment; institutions; corruption Romania